2017
DOI: 10.1021/acs.biochem.6b01208
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome Histone Tail Conformation and Dynamics: Impacts of Lysine Acetylation and a Nearby Minor Groove Benzo[a]pyrene-Derived Lesion

Abstract: Histone tails in nucleosomes play critical roles in regulation of many biological processes including chromatin compaction, transcription and DNA repair. Moreover, post-translational modifications, notably lysine acetylation, are crucial to these functions. While the tails have been intensively studied, how the structures and dynamics of tails are impacted by the presence of a nearby bulky DNA lesion is a frontier research area, and how these properties are impacted by tail lysine acetylation remains unexplore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 92 publications
1
19
0
Order By: Relevance
“…In this study, NCPs with acetylated H2B proteins showed an increase in product formation when compared to unmodified NCPs. While the H2B tail associates with the nearby DNA in unmodified NCPs, it has been shown that acetylation causes release of H2B tails from the DNA 43 . Further, FRET studies have shown that acetylation of histones facilitates DNA unwrapping 44, 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, NCPs with acetylated H2B proteins showed an increase in product formation when compared to unmodified NCPs. While the H2B tail associates with the nearby DNA in unmodified NCPs, it has been shown that acetylation causes release of H2B tails from the DNA 43 . Further, FRET studies have shown that acetylation of histones facilitates DNA unwrapping 44, 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the histone tails are prone to post-translational modifications such as lysine methylation, acetylation, phosphorylation or even ubiquitination which participate to the regulation of the chromatin compaction or the interaction with other proteins (transcription regulator, DNA repair complex) 45 . These modifications can alter the interaction between the damage and the tail 33 , or increase the reactivity of the abasic site 46 and should also be considered in future works to describe a wider panorama of DPC formations.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular dynamics has become a dominant method to shed insights on: structural 21 and mechanical properties 22 , reactivity and repair of AP sites 23 25 , and effects of clustered AP sites 26 , 27 . A few all-atom molecular dynamics simulations have been performed on NCPs, undamaged 28 30 , stacked 31 , with double-strand breaks 32 , or harboring acetylated histone tails 33 . As it has become possible to reach the microsecond range for such systems 34 , they can serve as a computational microscope 35 to probe the conformational and mechanical cross-talk between an abasic site and its N-DNA environment.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that acetylation of H2B increased hOGG1 activity for the outward 8-oxoG located off the dyad [52]. Indeed, it has been shown that while the H2B tail associates with the nearby DNA, acetylation causes release of the tail from the DNA which could allow for hOGG1 binding [53]. When considering microenvironments within an NCP another notable feature is that DNA in the dyad region lacks superhelical coils whereas repair in other regions could be confounded by the DNA superhelices.…”
Section: Glycosylase Activity In Ncpsmentioning
confidence: 99%